Fixed-dose combination antituberculosis therapy: a systematic review and meta-analysis - Amr S. Albanna; Benjamin M. Smith; Deanna Cowan; Dick Menzies (2013)
Fixed-dose combination (FDC) formulations are currently recommended for the treatment of active tuberculosis (TB). We have conducted a systematic review to evaluate the risk of treatment failure or disease relapse, acquired drug resistance, bacterial conversion after 2 months of treatment, adverse events, adherence and treatment satisfaction associated with treatment of active TB using FDC or separate drug formulations. We searched four electronic databases for randomised controlled trials and cohort studies. Results from trials that directly compared FDC to separate drug formulations were pooled. Results from other studies were reported separately. We identified 2450 citations from which 15 controlled trials and four additional relevant studies were included. In the 15 trials there were no differences in acquired drug resistance, bacterial conversion after 2 months of treatment or adverse drug reactions with FDC or separate drug formulations. There was a trend toward higher risk of failure or relapse with FDC (pooled relative risk 1.28 (95% CI 0.99–1.7)). Based on individual study results, only one of two trials that assessed treatment satisfaction, and none of five that assessed patient adherence, favoured FDCs. Although FDC formulations simplify TB therapy, the current evidence does not indicate that these formulations improve treatment outcomes among patients with active TB.